2013
DOI: 10.1007/s10461-013-0676-9
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Post-coital Intravaginal Cleansing for the Introduction of Vaginal Microbicides in South Africa

Abstract: Post-coital intravaginal cleansing (IVC) could counteract the protective effect of a vaginal microbicide. IVC less than 1 h after sex is discouraged in most microbicide trials. During a microbicide trial in KwaZulu-Natal, we collected quantitative data on post-coital IVC. We discussed IVC during in-depth-interviews (IDIs) and focus-group discussions (FGDs) with women enrolled in the trial, and during FGDs with community members. Nearly one-third (336/1,143) of women reported IVC less than an hour after sex. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Although oral PrEP in women has been shown to decrease risk of HIV acquisition when taken consistently, studies of PrEP in the form of vaginal gels have shown inconsistent efficacy to date [8,25]. It has yet to be determined if vaginal gels have been unsuccessful at reducing HIV acquisition because of poor adherence, biological factors, or potentially confounding by other practices such as IVPs [26]. Two studies of PrEP in the form of vaginal rings, The Ring Study and ASPIRE, are anticipated to provide results in 2016 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although oral PrEP in women has been shown to decrease risk of HIV acquisition when taken consistently, studies of PrEP in the form of vaginal gels have shown inconsistent efficacy to date [8,25]. It has yet to be determined if vaginal gels have been unsuccessful at reducing HIV acquisition because of poor adherence, biological factors, or potentially confounding by other practices such as IVPs [26]. Two studies of PrEP in the form of vaginal rings, The Ring Study and ASPIRE, are anticipated to provide results in 2016 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in this analysis we included interviews with 79 trial participants who were interviewed around the time of their week 4 visit. The interview guide has been described elsewhere and included the following topics: partner involvement in decisions relating to sexual matters and partner involvement in gel use [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been noted that because intravaginal practices present a risk of diluting efficacy through removing or interfering with microbicides, more work is needed to understand motivations and risk reduction around IVP in the context of effective microbicide use. 6 Conducting large-scale behavioral interventions on intravaginal cessation should be an important component to future microbicide trials conducted in areas in which intravaginal practices are prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…5 As outlined by the World Health Organization, 4 these include internal insertion of fingers and other substances including fluids (douching) into the vagina. 6 These practices are associated with a decreased abundance and proportion of Lactobacillus sp., increased BV, and higher risk for HIV-1. 7,8 In longitudinal follow-up of Kenyan FSWs, IVP increased HIV-1 risk *4-fold.…”
Section: Introductionmentioning
confidence: 99%